The rs7799039 variant in the leptin gene promoter drives insulin resistance through reduced serum leptin levels - Song, Yongyan; Zhang, Youjin; Liu, Xinyu; Gong, Wang; Ai, Yinquan; Shen, Binger; Li, Jing; He, Chuan (Frontiers in Endocrinology, 2025)
BackgroundThe associations between the rs7799039 variant in the promoter region of the leptin gene (LEP) and the rs1137100, rs1137101, and rs1805094 variants in the exons of the leptin receptor gene (LEPR) with leptin levels and glucose-lipid metabolism markers have been examined across various populations. However, the findings have been inconsistent and, at times, contradictory.MethodsEligible studies were identified through a search of PubMed, Google Scholar, Embase, Cochrane Library, Web of Science, CNKI, Wanfang, and VIP databases. A random-effects model was employed, and the standardized mean difference (SMD) with 95% confidence interval (95% CI) was calculated to assess the differences in leptin levels and glucose-lipid metabolism markers between subjects with different genotypes of the rs7799039, rs1137100, rs1137101, or rs1805094 variants. Heterogeneity among studies was evaluated using Cochran’s Q-test, based on the χ² statistic. Publication bias was assessed using Begg’s test.ResultsA total of 33 studies (10,471 subjects) for the rs7799039 variant, 12 studies (6,595 subjects) for the rs1137100 variant, 48 studies (18,890 subjects) for the rs1137101 variant, and 20 studies (5,051 subjects) for the rs1805094 variant were included in the pooled analyses. A significant association was found for A-allele carriers of LEP rs7799039 variant, who exhibited lower levels of leptin (SMD = -0.18 ng/mL, 95% CI = -0.31 to -0.04 ng/mL, p = 0.01), and higher levels of insulin (SMD = 0.22 μmol/μL, 95% CI = 0.07 to 0.37 μmol/μL, p < 0.01), and HOMA-IR (SMD = 0.26, 95% CI = 0.08 to 0.43, p < 0.01) compared to GG homozygotes. For LEPR rs1137100, rs1137101, and rs1805094 variants, no significant associations with leptin or glucose-lipid metabolism markers were observed in the pooled meta-analyses of the total population. However, significant associations were detected between the rs1137101 and rs1805094 variants and leptin or glucose-lipid metabolism markers in subgroup analyses stratified by sex, ethnicity, and health status.ConclusionsThe meta-analysis suggests that the A allele of LEP rs7799039 variant is associated with an increased risk of insulin resistance, potentially through its effect on reducing leptin levels. LEPR rs1137101 and rs1805094 variants show weak associations with leptin levels and glucose-lipid metabolism markers.Systematic review registration, identifier CRD42025373543.